A practical multi-objective design approach for optimum exhaust heat recovery from hybrid stand-alone PV-diesel power systems - Yousefi M.; Kim J.H.; Hooshyar D.; Yousefi M.; Sahari K.S.M.; Ahmad R.B. (Elsevier Ltd, 2023)
Electric power systems; Energy efficiency; Genetic algorithms; Local search (optimization); Solar energy; Solar power generation; Waste heat; HOMER; Local search; NSGA-II; Stand alone power systems; Thermoeconomic optimization; Design